A study of financial and operational performance of Qushai Enterprise / Asgar Jahan ... [et al.] - Jahan, Asgar; Kiprawie, Adli; Anthony Maramat, Edward Hutchinson; Abdul Aziz, Abu Bakar (2005)
The hospitality industry includes all establishments that provide food and beverages service to the public. Catering businesses have become one of the fastest growing segments of the food service industry not only in Malaysia but internationally. Changing population demographics and lifestyles in Malaysia and in Sarawak in particular have been a primary force behind this growth. Two income families, extended weekends and the increasing size of population nationwide, are a few of the major influences contributing to this growth trend. The result is an increased demand for professional food preparation and service to both small and large group gatherings in wide variety of settings.